Reactions to Prospective Positive vs. Negative Evaluation in the Laboratory: A Comparison of High and Low Socially Anxious Participants. Issue 4 (December 2016) - Barber, Kevin C.; Moscovitch, David A.
We present a study designed to investigate fear of positive vs. negative evaluation within the context of a laboratory-based paradigm designed to evoke social threat. Eighty-nine undergraduates with high (n = 43) or low (n = 46) levels of trait social anxiety took part in a "getting acquainted" task. Participants rated their anxiety about receiving prospective positive vs. negative evaluation in anticipation of receiving public feedback on a filmed introduction of themselves that they had made for an unknown social partner whom they expected they would later meet. Results demonstrated, in contrast to extant theories of fear of positive evaluation in social anxiety, that all participants, including those with high levels of social anxiety, rated the prospect of positive evaluation as anxiety reducing. This finding raises important questions about the construct of fear of positive evaluation and how to measure it "in vivo" in an ecologically valid manner.